Teachers’ Experiences and Challenges of Integrating ICTs in English Language Classrooms in Rural Schools of Nepal - Joshi, Khem Raj; Ayer, Ramesh (Journal of NELTA Gandaki, 2024)
This study explored the English language teachers' experiences of using Information Communication Tools (ICTs) in the rural schools' classrooms of Ramechhap district, Nepal. It mainly focused on three aspects: the exploration of the tools used by the teachers; the challenges in implementing ICTs; and the possible solutions to cope with the situations from the perspectives based on the teachers' experiences. Using a qualitative approach, through narrative inquiry, the research involved a series of unstructured interviews with five purposively selected participants. We have analysed the information descriptively and thematically. The findings indicate that the teachers utilised various ICTs including laptops, mobiles, multimedia projectors, websites, Facebook groups, PowerPoints, and printers to enhance the teaching/learning. However, several challenges were identified, such as heavy workloads, time constraints, maintenance issues, erratic electricity supply, inadequate ICT resources and financial limitations. To handle the situations, the teachers employed various strategies like selective ICT use, use of personal computers, advocacy with higher authorities, workshop organisation, and ensuring reliable electricity and internet connectivity. To integrate ICTs in teaching and mitigate those barriers, the study recommends focusing on teacher training programs, ensuring consistent and reliable internet access, maintaining an uninterrupted power supply, providing adequate financial support, and implementing systematic monitoring and evaluation mechanisms. By addressing these recommendations, educators in rural Nepal can potentially enhance their teaching effectiveness through improved ICT integration, thereby, facilitating better learning experiences for the students in English Language Teaching (ELT) classrooms.